Concepções e práticas de professores do Ensino Médio sobre a contextualização matemática com Função Afim - Lima, Jéssica Araújo de (2015)
This research has as its central theme a study on the concept and practice of high school teachers in the use of mathematics contextualization in the content of the Função Afim. With regard to methodology, it is an exploratory research, with qualitative field research. Data collection was performed using a semi-structured interview and the answers were obtained by written questionnaires and audio, where teachers were interviewed, five of them were from public school and two from private schools in the municipality of Mamanguape. In the theoretical framework was made a historical portrait of the formation of mathematics teachers and conceptual aspects and national guidelines on the mathematics of contextualization in high school were also brought, as well as the treatment for the Study of the Função Afim in High School. From the field research with teachers, it was noticed that the methodologies used in the classroom approach the curriculum guidelines on the use of mathematical context, since textbooks also bring this new proposal as well as the Exame Nacional do Ensino Médio - ENEM, which allows the teacher to adapt himself/herself to this teaching method more and more. However, we emphasize that the contextualization brought by these teachers are reduced to using everyday situations and do not use in a broad sense, considering the historical contextualization or with other areas of knowledge.